RISK OF LOSS OF COMMERCIAL BANK S BUSINESS REPUTATION: REASONS AND CONSEQUENCES - Igor Kunitsyn (Вестник Северо-Кавказского федерального университета)
Categorical differences of risk of loss of commercial bank's business reputation and reputation risk are considered. The reasons leading to loss of business reputation of the credit organization are studied, their group is performed. Classification of reputation risks of bank by a number of the bases is carried out.